PENERAPAN MODEL TWO STAY TWO STRAY UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS IV MIN 31 PIDIE - Syarifah Rahmi; Aminah (JURNAL EKSPERIMENTAL : Media Ilmiah Pendidikan, 2019)
This study aims to determine how the application of the cooperative learning model Type Two Stay Two Stray can improve learning outcomes of students in 4th grade of MIN 31 Pidie. This type of research is classroom action research. With a KKM value of 70 for natural science subjects, the results of the first cycle of action research conducted with an average value of 63.00 in the second cycle obtained an average value of 71.6 while in the third cycle obtained an average value of 87. Completeness of student learning outcomes in the first cycle the grades above KKM were 5 with a percentage of 25%, in the second cycle the grades above the KKM were 10 students with a percentage of 50%, and in the third cycle the grades above the KKM were 20 students with a percentage of 100%. Thus, it can be concluded that the application of the Cooperative Type Two Stay Two Stray (TSTS) model on the material benefits of energy can improve student learning outcomes in class IV MIN 31 Pidie.